Experimental pathology of two highly pathogenic H5N1 viruses isolated from crows in BALB/c mice. (April 2020) - Kombiah, Subbiah; Kumar, Manoj; Murugkar, Harshad Vinayakrao; Nagarajan, Shanmugasundaram; Tosh, Chakradhar; Senthil Kumar, Dhanapal; Rajukumar, Katherukamem; Gautam, Siddharth; Singh, Rajendra; Karikalan, Mathesh; Sharma, Anil Kumar; Singh, Vijendra Pal
Abstract: In this study, we assessed the pathogenicity of two H5N1 viruses isolated from crows in mice. Eighteen 6–8 weeks BALB/c mice each were intranasally inoculated with 10 6 EID50 /ml of H5N1 viruses A/crow/India/03CA04/2015 (H9N2-PB2 reassortant H5N1) and A/crow/India/02CA01/2012 (Non-reassortant H5N1). The infected mice showed dullness, weight loss and ruffled fur coat. Histopathological examination of lungs showed severe congestion, haemorrhage, thrombus, fibrinous exudate in perivascular area, interstitial septal thickening, bronchiolitis and alveolitis leading to severe pneumonic changes and these lesions were less pronounced in reassortant virus infected mice. Viral replication was demonstrated in nasal mucosa, lungs, trachea and brain in both the groups. Brain, lung, nasal mucosa and trachea showed significantly higher viral RNA copies and presence of antigen in immunohistochemistry in both the groups. This study concludes that both the crow viruses caused morbidity and mortality in mice and the viruses were phenotypically highly virulent in mice. The H5N1 viruses isolated from synanthropes pose a serious public health concern and should be monitored continuously for their human spill-over. Highlights: H5N1 highly pathogenic avian influenza viruses isolated from crows in India caused significant pathology in BALB/c mice. Non-reassortant H5N1 virus caused more severe lesions compared to H9N2-PB2 reassortant H5N1 virus in mice. The H5N1 viruses in crows pose a significant public health concern as crows harbour near human dwellings.